2017
DOI: 10.3389/fpsyg.2017.01240
|View full text |Cite|
|
Sign up to set email alerts
|

Exposure to Parenting by Lying in Childhood: Associations with Negative Outcomes in Adulthood

Abstract: Parents around the world engage in the practice of parenting by lying, which entails lying to manipulate children’s emotional states and behavior. The current study is the first to examine whether exposure to parenting by lying in childhood is associated with later dishonesty and psychosocial maladjustment in adulthood. Female undergraduate adults retrospectively reported their experiences of parenting by lying during childhood, the current frequency at which they lie to their parents, and their current psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 28 publications
2
27
0
1
Order By: Relevance
“…Recent research suggests that parental lying may have implications for children’s mental health (Heyman et al, 2013; Santos et al, 2017; Setoh et al, 2020). For example, Setoh et al (2020) examined young adults in Singapore and found that reports of high levels of childhood exposure to self-oriented lying from parents predicted higher levels of externalizing problems, internalizing problems, and psychopathic attributes in adulthood.…”
Section: Parental Lying Behaviorsmentioning
confidence: 99%
“…Recent research suggests that parental lying may have implications for children’s mental health (Heyman et al, 2013; Santos et al, 2017; Setoh et al, 2020). For example, Setoh et al (2020) examined young adults in Singapore and found that reports of high levels of childhood exposure to self-oriented lying from parents predicted higher levels of externalizing problems, internalizing problems, and psychopathic attributes in adulthood.…”
Section: Parental Lying Behaviorsmentioning
confidence: 99%
“…Moreover, the effects of parents' lies to gain their children's compliance appear to be enduring. Adults who reported that their parents lied to them to solicit desired behaviours in childhood also reported lying to their parents in adulthood, and the more they experienced parenting by lying, the more they lied (Santos, Zanette, Kwok, Heyman, & Lee, 2017; Setoh, Zhao, Santos, Heyman, & Lee, 2020). Parenting by lying may lead to increased lie‐telling because it hinders value internalization.…”
Section: The Domains‐of‐socialization Frameworkmentioning
confidence: 99%
“…In fact, most recent studies argue that the condition necessary to clearly demonstrate and justify the presence of a mediating effect between two variables of interest, is to confirm the significance of an indirect effect between the two, regardless of the presence of “an effect to be mediated” ( Hayes, 2009 , 2013 ; Preacher et al, 2007 ; Zhao et al, 2010 ). This approach has been gaining increasing popularity in the organizational and psychology literature (e.g., Mostafa & Bottomley, 2018 ; Romani, Grappi, & Bagozzi, 2013 ; Santos, Zanette, Kwok, Heyman, & Lee, 2017 ) as it allows for more rigorous testing of mediating effects.…”
Section: Methodsmentioning
confidence: 99%